The first human fossil from the Ruidera site (Castilla-La Mancha, Spain): A partial parietal and its implications for Middle Pleistocene hominin variability in Southern Europe - D. García-Martínez; C. Buenestado Ruíz; S. Díaz Pérez; M. Bastir; L. Bermejo Albarrán; I. Campaña; O. Cambra-Moo; G. Cifuentes-Alcobendas; M. del Val; M. Duval; M.D. D'Angelo del Campo; B. Fernández Cascón; et al. (Journal of Human Evolution, 2026)

Test-Retest Reliability of Single Leg Jump Performance Using the Drift Protocol in Division I Baseball Pitchers - Amy M. Bergquist; Modesto A. Lebron; L. Colby Mangum; Jeffrey R. Stout; David H. Fukuda (Journal of Science in Sport and Exercise, 2025)

Standard area diagram set for anthracnose severity on grapevine bunches and shoots - L. R. Modesto; D. R. M. Steiner; J. K. Menon; R. O. Nodari; L. J. Welter; A. L. da Silva (Australasian Plant Pathology, 2020)

Serological and virological survey of hepatitis E virus in wild boar populations in northwestern Italy: detection of HEV subtypes 3e and 3f - Claudio Caruso; P. Modesto; S. Bertolini; S. Peletto; P. L. Acutis; A. Dondo; S. Robetto; W. Mignone; R. Orusa; G. Ru; L. Masoero (Archives of Virology, 2015)

Association of a specific major histocompatibility complex class IIβ single nucleotide polymorphism with resistance to lactococcosis in rainbow trout, O ncorhynchus mykiss (Walbaum) - S Colussi; M Prearo; S A Bertuzzi; T Scanzio; S Peletto; L Favaro; P Modesto; M G Maniaci; G Ru; R Desiato; P L Acutis (Journal of Fish Diseases, 2015)
Major histocompatibility complex ( MHC ) loci encode glycoproteins that bind to foreign peptides and initiate immune responses through their interaction with T cells. MHC class II molecules are heterodimers consisting of α and β chains encoded by extremely variable genes; variation in exon 2 is responsible for the majority of observed polymorphisms, mostly concentrated in the codons specifying the peptide‐binding region. L actococcus garvieae is the causative agent of lactococcosis, a warm‐water bacterial infection pathogenic for cultured freshwater and marine fish. It causes considerable economic losses, limiting the profitability and development of fish industries in general and the intensive production of rainbow trout, O ncorhynchus mykiss (Walbaum), in particular. The disease is currently controlled with vaccines and antibiotics; however, vaccines have short‐term efficacy, and increasing concerns regarding antibiotic residues have called for alternative strategies. To explore the involvement of the MHC class II β‐1 domain as a candidate gene for resistance to lactococcosis, we exposed 400 rainbow trout to naturally contaminated water. One single nucleotide polymorphism ( SNP ) and one haplotype were associated with resistance ( P MHC class IIβ as a molecular marker in breeding rainbow trout resistant to lactococcosis.

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)